Audit Apakah Urutan Bukti Audit dan Tindakan Supervisi Mempengaruhi Ketepatan Auditor Menilai Bukti Audit? (Penelitian Eksperimental) - Illa Susilawati; Apandi, R. Nelly; Widarsono, Agus (APSSAI, 2022)
The study was intended to see how the sequence of audit evidence and supervision actions could affect the precision of the auditor by viewing from the standpoint of the auditory evidence. The study was conducted with 41 students of the Indonesian University of Education Accounting program (UPI) students of 2018. Research methods are conducted with experiments. Research design in this research using vectorial design by 2x2. Studies have shown that the sequence of audit evidence has an effect on the appropriateness of the auditing evidence, whereas the actions of supervision have no bearing on the correctness of the auditing evidence. Studies between the sequence of evidence and the actions of supervision both had no effect on the correctness of the auditors. The results of research implicates a person's process of auditor candidate position himself as the one capable of assessing audit evidence.